Water-adsorption effect on electrical resistivity of nanoporous gold. (October 2016) - Hakamada, Masataka; Kato, Naoki; Miyazawa, Naoki; Mabuchi, Mamoru
Abstract: The effect of water adsorption on the electrical resistivity of nanoporous gold (NPG) thin films, as well as flat gold (FG) with no nanoporosity, has been examined. Both NPG and FG thin films showed higher electrical resistivity in water than in air; however, the difference between the electrical resistivity of NPG in water and in air was quite large. The first-principles calculations suggest that the density of states at Fermi energy of the surface gold atoms decreases as a result of water adsorption, which is responsible for the electrical resistivity change in the NPG. Graphical abstract: